Keragaman Genetik berbagai Isolat Beauveria bassiana (Bals.) Vuill. (Deuteromycotina: Hyphomycetes) dan Virulensinya terhadap Crocidolomia pavonana - Trizelia, Trizelia; Santoso, Teguh; Sosromarsono, Soemartono; Rauf, Aunu; Sudirman, Lisdar I (Jurnal Natur Indonesia, 2012)
The objectives of the research were to study the genetic variability of various Beauveria bassiana (Bals.) Vuill. isolates andvirulence to Crocidolomia pavonana. Thirteen isolates of B. bassiana were isolated from Nilaparvata lugens (Stål),Leptocorisa oratorius (F.), Thrips sp., Hypothenemus hampei (Ferr.), Crocidolomia pavonana (F.), Spodoptera litura (F.),Chrysodeixis chalcites (Esp.), and Riptortus linearis (L.) pests from different geographical locations in Indonesia. Fourteendifferent random primers were used to amplify DNA. Clustering of isolates were obtained using Unweight Pair GroupMethod Avarage (UPGMA). The results showed that only OPA08 primer generated more polymorphic DNA fragments.Result of clustering analysis showed that B. bassiana isolates forms two groups having genetic similarity equal to 55%.Clustering of isolates does not correlate to host type nor geographic origin. Mortality of second instar C. pavonana larvaewas dependent on the fungal isolates. At a concentration of 108 conidia/ml, isolate Bb-La2 had the highest virulence whichcaused 65% mortality of 2nd instar larvae. Isolates of B. bassiana is virulent against C. pavonana larvae present in the samegenotype group.